THE DEVELOPMENT OF THE ENGINEERING DESIGN PROGRAM AT THE UNIVERSITY OF FORESTRY FROM THE VIEWPOINT OF ITS GRADUATES (Innovation in Woodworking Industry and Engineering design, 2026)
The article represents a unique view at how the “Engineering Design (Interior and Furniture Design)” Program developed from its inception to the present times. The authors of the article hold a Master Degree in Engineer Design from the first cohort; later, they defended their PhD thesis in the same field. Nowadays, they act in the position of Lecturers, training students of the same Program. All of this gives a unique look at the various achievements and problems that have arisen during the Design Program's development period. Aspects such as the kind of studied courses, teaching methods, facilities, opportunity for creative expression, and students' career prospects are considered. For better objectivity, the opinion of other alumni who graduated the Program over the years has been studied.